A Preparation Of Format And Presentation Media For English Learning In Merdeka Curriculum - Siti Rahmawati; Zaitun Qamariah (PT. Padang Tekno Corp, 2023)
This study aims to analyze the format for the preparation of the Curriculum Merdeka and the appropriate presentation media for this curriculum. A format preparation is a decision made about learning objectives and the strategies and methods needed to achieve these goals as well as a study of the effectiveness and meaning of these methods and strategies. In addition, the Government gives authority to schools to make their vision, mission and characteristics a reference for operational curriculum development. Presentation media is said to be a graphic, photographic tool, and can also be in the form of an electronic device that has the function of capturing, processing and rearranging information in the form of verbal or visual. English learning is developing English language skills in a contextual and acceptable manner according to the context and conditions and situations of students' daily lives. This is to produce a form of learning English that is more in touch with the language needs of students. Curriculum Merdeka is a curriculum which in its development is the result of adjustments to the latest conditions in an area and in accordance with the development of students due to contemporary issues that are currently happening. This research is use method literature study. Data collected and analyzed entirely from the literature as well as other documentation materials, such as writing in journals or other media relevant and still being studied.